JENIS DAN KANDUNGAN ANTOSIANIN BUAH TOMI–TOMI - Rema Fitriyani; Lydia Ninan Lestario; Yohanes Martono (Jurnal Teknologi dan Industri Pangan, 2018)
Batoko plum fruit (Flacourtia inermis, Roxb) is one of the plants that contains anthocyanins. The fruit has purplish red color and was thought to benefit health by reducing blood sugar levels, as anti-hyperten-sion agents or antioxidants. The aim of this research was to determine the total anthocyanin content and identify the type of anthocyanidin and anthocyanin of batoko plum fruit. The total anthocyanin content of batoko plum fruit which determined by differential pH method was 26.56±0.28 mg/100 g (w.b.) or 103.89±1.08 mg/100 g (d.b.). Based on the Rf value on TLC and the peak retention time in HPLC, it was confirmed that the anthocyanin was delfinidine. However, the wavelength maximum absorbance data of the TLC spot showed  the presence of cyanidine. These results were possibly caused by the use of too diluted extracts or the degradation of the anthocyanin during acid hydrolysis. Based on the Rf value on TLC and glucosidation pattern in UV-VIS spectrophotometer, it is suspected that cyanidine 3-glucoside and delfinidine 3-glucoside were present.